BSA adsorption, antibiofilm and antifouling studies of N-tert-amylacrylamide based hydrogels - Krishnasami Jayanthi; Periyasamy Pazhanisamy; Kasi Chithra; William Shanthi; Arumugam Venkatesan; Dhurairaj Satheesh (Hybrid Advances)
Because of their special qualities—such as their high water content, softness, flexibility, and biocompatibility—hydrogels have grown in popularity. Hydrogels can be created by physically or chemically cross-linking hydrophilic polymers, both natural and manufactured. Because of their similarity to live tissue, they have a wide range of potential uses in the biomedical field. Hydrogels are being utilized in the production of wound dressings, tissue engineering scaffolds, contact lenses, hygiene products, and medication delivery systems. Polymer crosslinking can be used to create hydrogels. Using free-radical copolymerization of N-tert-amyl acrylamide (NTA), acrylamide AM, and maleic acid (MA)/N-iso-propyl acrylamide (NIPAM)/acrylic acid (Ac) as monomers in a methanol/water mixture (3:1 ratio) at 60 °C, we created the N-tert-amylacrylamide base hydrogels (HG1-HG4, HG13-HG16, and HG25-HG28) in this study. FT-IR, PXRD, SEM-EDX, and TGA studies were used to characterise the produced hydrogels. The synthesized hydrogels' BSA adsorption was examined at varied pH values and with varying concentrations of MA, NIPAM, and Ac. PXRD, SEM, and TGA were also used to compare hydrogels before and after BSA adsorption. Protein adsorption results from hydrogel surfaces' ability to soak in liquids. Research on the adsorption of BSA in hydrogels revealed that the highest adsorption occurred at pH 5.0, which is near the BSA's isoelectric point (IEP). When MA, NIPAM, and Ac were the third monomers, the BSA adsorption amounts at pH 5.0 were 116.4 mg/g, 129.4 mg/g, and 112.0 mg/g, respectively. At 129.4 mg/g, the poly(NTA-co-AM/NIPAM) hydrogel exhibited the highest BSA adsorption. Sharpened peaks were visible in the XRD, fewer holes were visible in the SEM pictures, and a different breakdown temperature was indicated by the TGA. BSA adsorption was enhanced and conformed by all of these methods. They also showed that following protein adsorption, the hydrogels' amorphous character diminished. Using the MTP assay, the antibiofilm behaviour of hydrogels was investigated in vitro. The hydrogels resisted the biofilm formed by Pseudomonas aeruginosa and Staphylococcus aureus in vitro because of their anionic nature and hydrophilia, which increases their swelling capacity. When MA, NIPAM, Ac, and AMPSNa were the third monomer, the synthesized hydrogels' IC50 values were 24.98 μg/mL, 27.15 μg/mL, 25.06 μg/mL, and 20.45 μg/mL against S. aureus and 46.78 μg/mL, 48.16 μg/mL, 47.72 μg/mL, and 46.64 μg/mL against P. auregiosa, respectively. Because of its ionic nature and greater hydrophilicity, poly(NTA-co-AM/AMPSNa) hydrogel exhibits a stronger inhibition. The nature of biofilm inhibition was further demonstrated by SEM and fluorescence microscopy. The antibiofouling property against the marine alga Ulva Lactuca was evaluated invitro and this property was due to hydrogen bonding which forms the energy barrier for the spores to get attached.